(untitled) (CIPEEX, 2024)
FEMORAL NECK FRACTURES ARE ONE OF THE MOST COMMON MUSCULOSKELETAL PROBLEMS IN THE ELDERLY POPULATION AND ARE ALSO A WORLDWIDE PROBLEM WITH CONSEQUENCES FOR THE HEALTH CARE SYSTEM THAT LEAD TO AN INCREASE IN THE PERSON’S DEPENDENCE ON ACTIVITIES OF DAILY LIVING. MOST CASES REQUIRE HOSPITAL ADMISSION, SURGICAL INTERVENTION AND LONG-TERM REHABILITATION. THUS, THIS WORK AIMS TO ANALYZE THE INCIDENCE OF FRACTURES IN THE FEMORAL NECK IN ELDERLY PEOPLE ADMITTED TO THE CERES ORTHOPEDIC HOSPITAL - GO (HOC), BETWEEN THE YEARS 2019 AND 2022, HIGHLIGHTING THE MOST AFFECTED AGE GROUPS, GENDER AND WHETHER THE TREATMENT WAS CARRIED OUT THROUGH THE UNIFIED HEALTH SYSTEM (SUS) OR PRIVATE HEALTH PLAN. THE RESEARCH WILL BE CARRIED OUT THROUGH A CROSS-SECTIONAL DATA COLLECTION STUDY WITH A QUANTITATIVE ASPECT, AND THE DATA WILL BE COLLECTED AT THE HOC VIA DIGITAL RECORDS, AUTHORIZED BY THE HOSPITAL UNIT. THEREFORE, THIS RESEARCH WILL ENABLE DATA COLLECTION, ASSUMING THE IDENTIFICATION OF THE AGE GROUP, GENDER AND YEAR IN WHICH THE INCIDENCE OF FEMORAL NECK FRACTURES IN THE ELDERLY WAS MOST AFFECTED. FURTHERMORE, THE RESULTS OBTAINED WILL BE DISSEMINATED TO THE POPULATION THROUGH ARTICLES AND LECTURES, HIGHLIGHTING THE IMPORTANCE OF FALL PREVENTION CAMPAIGNS AND BONE DENSITOMETRY TESTS TO CHECK CALCIUM IN BONES.